2017
DOI: 10.1002/adma.201603233
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Origami‐Driven Lithography for Patterning on Gold Surfaces with Sub‐10 nm Resolution

Abstract: The programmability [1] and self-assembly properties of DNA provides means of precise organization of matter at the nanoscale. [2] DNA origami allows the folding of DNA into twodimensional [3] and three-dimensional [4] structures, and has been used to organize biomolecules, [2b, e, 5] nanophotonic [2a, c, f, 6] and electronic [7] components with a resolution of 6 nm / pixel. [8] Two-dimensional DNA origami has been also used as a platform to organize other chemical [9] species that can then be placed on tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…36 We would like to point out that this ability deterministically limit steric hindrance through printed deposition would be particularly beneficial for precise arrangements of larger objects of a non-biological nature. Previous reported results [22][23][24] and our own studies have shown a similar technique applied to large gold nanoparticles, supporting the broadness of this asset. As described in more detail in ESI section 2, † we used a similar strategy as with previous studies to directly deposit thiol-functionalised DNA strands onto bare gold substrates.…”
Section: Nanoscale Papersupporting
confidence: 80%
See 2 more Smart Citations
“…36 We would like to point out that this ability deterministically limit steric hindrance through printed deposition would be particularly beneficial for precise arrangements of larger objects of a non-biological nature. Previous reported results [22][23][24] and our own studies have shown a similar technique applied to large gold nanoparticles, supporting the broadness of this asset. As described in more detail in ESI section 2, † we used a similar strategy as with previous studies to directly deposit thiol-functionalised DNA strands onto bare gold substrates.…”
Section: Nanoscale Papersupporting
confidence: 80%
“…However, direct covalent attachment of proteins to the SAM could be implemented through a secondary conjugation between the protein and an orthogonal reactive group on a two-component SAM. 38 Most importantly, in contrast to a printing onto bare gold surfaces [22][23][24] this generalised approach of printing onto a predeposited SAM enables the overall principle to be universally applied to nearly any type of substrate material where a stable (see ESI note 2.3 †), functional monolayer can be covalently or even non-covalently deposited. This opens the door for fabricating functional, nanometer-precise, single-molecule arrays on two-dimensional materials such as graphene and dichalcogenides, silanised silicates, ceramics, other metals such as titanium, semi-conducting substrates like ITO or even cheap plastics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis of the distribution of nanoparticle alignment showed a decay of the frequency upon increment of number of OGNP in a chain and that the apparent, statistically significant maximum number of particles in a chain was significantly below to the 12 DNA ink programmed on the printed pattern [5]. The statistical analysis and Monte Carlo simulations were used to create a computational model.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, DNA origami methodology has not been utilized to transfer and covalently bind the patterns on surfaces with sub-10 nm resolution. Herein we report on the use of a two-dimensional DNA origami as a template that bears pre-programmed patterns that can be lithographically transferred to a surface [5] (Figure 1). …”
Section: Introductionmentioning
confidence: 99%